THE CORRELATION BETWEEN JOB-HOPPING ATTITUDE AND TURNOVER BEHAVIOR: A JOB SATISFACTION PERSPECTIVE IN BANGLADESH - Ali, Md. Chapol; Islam, K. M. Anwarul; Chung, Soo-Jin; Zayed, Nurul Mohammad; Islam, Mohammad Rakibul (International Journal of Business and Management Future, 2021)
A worker is a company’s principal power base. Recently, the employment and turnover rates of employees have risen very high for several reasons. It was still a matter of great importance to organizations. This study focuses on the multiple reasons for work saving and turnover behaviors at different workers levels in Bangladesh. This research focuses on various factors. Through this hypothesis, the key methods to determine the independent variables are studied, including worker satisfaction, job quality, employee facilities, and employee dependent variables, employment and turnover rates. A correlation between the independent and dependent variables has been identified. A survey of 150 respondents working at various levels in Bangladeshi organizations was performed with the hypothesis-based questioner. The data obtained through the survey and statistically analyzed using tools for data analysis (SPSS). In this study, the relationship between independent variables and dependent variables was analyzed through descriptive statistics, reliability analysis and inference analysis. The study of linear and multi-linear regression on these parameters indicates the purpose of the reversal. Based on the results; the theoretical issues will be validated. This study explores the key explanation for this and establishes a research paradigm to minimize Bangladesh’s high turnover.JEL Classification Codes: J62, J28, J63.